A Preliminary Study of the Pteridophytes, Gymnosperms, and Monocotyledons in the Chapainawabganj District’s Flora of Bangladesh (Bangladesh Journal of Plant Taxonomy, 2024)
This study demonstrates that the vascular flora (Pteridophytes, Gymnosperms, and Monocotyledons) of the Chapainawabganj district area consists of 247 species with two subspecies under 126 genera and 35 families. The pteridophytes and gymnosperms are represented by 19 and four species, respectively, whereas the monocotyledons (Liliopsida) are represented by 224 species. Poaceae, with 91 species, representing 36.84% of the flora, appears to be the largest family, followed by Cyperaceae 32, Araceae 19, Asparagaceae 12, and Arecaceae 11, which collectively constitute ca. 30% of this flora. Cyperus, comprising 18 species, is recorded as the largest genus, followed by Fimbristylis, Digitaria, Panicum, Bambusa, Urochloa, Dracaena, and Dioscorea. About 87.55% of this flora’s taxa are herbs, 4.42% are palms, 3.61% are shrubs, and the rest are bamboos and trees. Erect herbs, forming 61.04% of the flora, comprise the most common life form. In this flora, almost 74.30% of the taxa are native, and the rest, 25.70%, are exotic. It is found that nearly 74.70% of the taxa are wild, 14.06% are planted, and 11.24% are cultivated. About 23.29% of taxa commonly occur throughout all upazilas in this district. Most of the species are harboured in fallow lands, roadsides, gardens, and homesteads. All species of this district's flora are known to be economically useful. Most of its habitats and ecosystems are exposed to different threats. Adequate measures with effective management plans should be adopted and implemented for the sustainable use, improvement, and conservation of this precious flora.Bangladesh J. Plant Taxon. 31(1): 83-99, 2024 (June)